Heart Failure Due to "Disappearing" Aortic Valve in Hypoplastic Left Heart Syndrome. (April 2014) - Loftus, Patrick D.; Erickson, Lance K.; Everitt, Melanie D.; Kaza, Aditya K.
We present the unusual case of a "disappearing" aortic valve in an infant with hypoplastic left heart syndrome (mitral and aortic stenosis) that underwent Norwood palliation at birth and subsequently a Glenn operation. Angiographic images at the time of operation showed no apparent insufficiency of the native aortic valve. Over the course of 14 months following operation, the patient developed significant cardiomegaly with a workup revealing severe native aortic valve insufficiency. Following orthotopic heart transplantation, examination of the explanted heart revealed a complete absence of native aortic valve leaflets.